2020
DOI: 10.1111/1346-8138.15679
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of severe congenital hypotrichosis caused by compound heterozygous mutations in the LSS gene

Abstract: It has recently been shown that bi‐allelic mutations in the lanosterol synthase (LSS) gene, which was originally reported as a causative gene for congenital cataracts, underlie a non‐syndromic form of hypotrichosis. Furthermore, it has also been revealed that mutations in the LSS gene can cause syndromic forms of hypotrichosis. To date, however, clear genotype–phenotype correlations have not completely been characterized. In this study, we identified two Japanese patients who had severe congenital hypotrichosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 15 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Both parents were heterozygous carriers of the mutation (Figure 1a). Recent studies reported this mutation occurring in a compound heterozygous state, together with other mutations, in two further hypotrichosis patients, who presented with and without ID, respectively (Murata et al, 2021;Wada et al, 2020).…”
mentioning
confidence: 92%
“…Both parents were heterozygous carriers of the mutation (Figure 1a). Recent studies reported this mutation occurring in a compound heterozygous state, together with other mutations, in two further hypotrichosis patients, who presented with and without ID, respectively (Murata et al, 2021;Wada et al, 2020).…”
mentioning
confidence: 92%
“…13 Several families with the HS phenotype have been described with the variants spread across both domains. [8][9][10][11]14,18 Then the phenotypic spectrum of LSS was expanded to include a third and more severe neuro-ectodermal phenotype, APMR4, with a report of 11 patients from seven unrelated families having alopecia and intellectual disability secondary to LSS biallelic variants. 2 The described LSS variants were distributed across both LSS domains thus providing no clear phenotype-genotype correlation (Figure 1D).…”
Section: Romano Et Al Described a Number Of Cases From Different Ethnic-mentioning
confidence: 99%
“…6 A total of 29 families with all three LSS-related disorders have been reported worldwide amongst which are 10 families with 15 affected individuals with the APMR4 phenotype. 2,5,[7][8][9][10][11][12][13][14][15][16][17][18] We describe an Egyptian patient with biallelic novel variants in LSS and APMR4 to potentially expand the mutational and phenotypic spectrum of the syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biallelic mutations in LSS were first reported in families with congenital cataracts (Zhao et al, 2015;Romano et al, 2018). More recently, several studies have identified mutations in the lanosterol synthase encoding gene LSS from patients affected by hypotrichosis simplex, suggesting LSS could also be associated with the disease (Li et al, 2019;Cesarato et al, 2021;Murata et al, 2021). Nevertheless, the pathophysiological mechanism of how its mutations cause hypotrichosis simplex remains unclear.…”
Section: Introductionmentioning
confidence: 99%